Analysis of 19,116 cases of human papillomavirus infection and subtype distribution in Sanmen, Zhejiang Province, China - Xuedan Lin; Yanchao Liu; Tianxing Yang (BMC Infectious Diseases)
Abstract Objective To analyze the prevalence and subtype distribution of human papillomavirus (HPV) infection in Sanmen County, Zhejiang Province, China, and the correlation between ThinPrep cytologic test (TCT) results. Methods A retrospective analysis was conducted on the demographic and clinical data of patients who underwent HPV typing and TCT at Sanmen People’s Hospital from January 2020 to December 2022. The HPV infection rate in the region was calculated, and the HPV infection status among patients in different age groups and departments was compared, as well as the relationship between different HPV types and TCT results. Results A total of 19,116 patients were included in the study. The overall HPV infection rate was 16.3%, single-type of infection accounted for 82.7% and multiple-type of infection accounted for 17.3%, with a high-risk type infection rate of 12.6% and a low-risk type infection rate of 2.7%. The top six HPV types in positive cases were type 52 at 24.3%, type 58 at 13.4%, type 53 at 12.5%, type 81 at 9.0%, type 16 at 7.3%, and type 68 at 5.8%. The results revealed a significant difference in HPV infection rates among age groups, with the < 25-year group having the highest infection rate at 21.1%. The proportion of abnormal TCT results was 8.0%, there was no significant difference in the comparison of abnormal TCT results among age groups, and no cases of high-grade squamous intraepithelial lesions were found in the < 25-year group. HPV type 16 had the highest positivity rate in cases of high-grade squamous intraepithelial lesion group. Conclusion HPV infection in the region is mainly single-type. The most common types were high-risk HPV 52, 58, and 53, with the highest HPV infection rate found in the < 25-year group. High-grade squamous intraepithelial lesion were closely related to infections with HPV 16, 58, 52, and 18.